ANALISIS HUBUNGAN ANTARA DIGITAL ENTREPRENEURSHIP, MARKETING MIX DAN TAM, TERHADAP KINERJA PEMASARAN BUMDES NERANG JAYA - Fikri, Zakaria; Ratih Hesty Utami; Qristin Violinda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research is motivated by the performance of BUMDES marketing during the 4.0 revolution, entering the era of modern development of digital information and communication technology, especially the internet, which seems to be a primary human need and is almost involved in daily activities. In today's all-digital situation, the right promotion strategy is needed to increase sales. The purpose of this study was to determine the effect of digital entrepreneurship, marketing mix and technology acceptance models on the marketing performance of BUMDES Nerang Jaya. The quantitative method used is a technique of collecting, processing, simplifying, presenting and analyzing data in order to provide an overview of an event through the distribution of questionnaires which are carried out and expressed in the form of numbers, so that they can be measured and calculated. The number of samples used were 95 respondents. This study uses the SmartPLS 3.0 program to process data